Analisis Dampak Obesitas pada Anak Usia Sekolah dan Kebijakan Pengurangan Angka Kasus Obesitas melalui Edukasi Gizi: Literature Review - Putri Wulandari; Marniati Marniati; Mega Putri Silvia (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
A comprehensive analysis of the impact of obesity on school-age children as well as the effectiveness of nutrition education interventions in an effort to mitigate its prevalence. Child obesity, which is based on Body Mass Index (BMI) above 2 standard deviation (SD), has broad implications for physical, social, emotional, and self-esteem health. This condition is also associated with decreased academic performance, reduced quality of life, limb growth disorders, sleep disfunction, sleep apnoea, respiratory complications, as well as accelerated bone maturation and sexual maturity.The findings show that school-based nutrition education is an effective strategy in increasing knowledge and delivery of nutrition interventions, especially when supported by all elements of the school. The duration and frequency of exposure to interventions are crucial factors for the success of nutrition education in triggering behavioural changes. Therefore, the prevention and management of obesity in children through structured nutrition education is essential.